2020
DOI: 10.3390/ma13204631
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Parent Concrete Properties on Compressive Strength and Chloride Diffusion Coefficient of Concrete with Strengthened Recycled Aggregates

Abstract: Parent concrete coming from a wide range of sources can result in considerable differences in the properties of recycled coarse aggregate (RCA). In this study, the RCAs were obtained by crushing the parent concrete with water-to-cement ratios (W/Cparent) of 0.4, 0.5 and 0.6, respectively, and were strengthened by carbonation and nano-silica slurry wrapping methods. It was found that when W/Cparen was 0.3, 0.4 and 0.5, respectively, compared with the mortar in the untreated RCA, the capillary porosity of the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 46 publications
0
8
0
1
Order By: Relevance
“…The above results suggest that both the curing methods can significantly decrease the crushing index of RCA, and it shows slight improvement in the water absorption, apparent density and void fraction. This is because CO 2 and nano-SiO 2 reacted with CH in the mortar attached to the surface of the aggregate to generate CaCO 3 and C–S–H, respectively, thus filling the excessive pores in the mortar attached to the surface of aggregate and improving the quality of RCA [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…The above results suggest that both the curing methods can significantly decrease the crushing index of RCA, and it shows slight improvement in the water absorption, apparent density and void fraction. This is because CO 2 and nano-SiO 2 reacted with CH in the mortar attached to the surface of the aggregate to generate CaCO 3 and C–S–H, respectively, thus filling the excessive pores in the mortar attached to the surface of aggregate and improving the quality of RCA [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Dado que la zona más débil de las ZIT son los puntos de contacto entre el mortero adherido y la matriz cementicia, es la zona donde se suelen producir los problemas de adhesión entre ambos materiales/fases (39). Un mortero adherido de mayor resistencia, posible gracias al uso de un hormigón de partida de mayor resistencia, hace que esta zona sea menos sensible a la aplicación de una fuerza y que el fallo no se produzca tan fácilmente (40). • En segundo lugar, en los casos en los que el AHR se rompe en vez de experimentar fenómenos de despegue, es evidente que la situación más beneficiosa es la presencia de un mortero adherido que tenga la mayor resistencia posible (41).…”
Section: Propiedades Del Hormigón De Partidaunclassified
“…Certain properties of the pores including size, tortuosity, and total porosity are highly correlated with chloride penetration. Although there have been some attempts to propose relationships between the pore structure and chloride diffusivity within concrete, the outcomes varied among several research groups [18][19][20][21][22] . For example, Zhang et al [23] demonstrated that there was a close correlation between DCland pore structure parameters including the total specific pore volume and the most probable pore diameter, as measured by MIP.…”
Section: Introductionmentioning
confidence: 99%